A study to determine the effects of epidural analgesia in labour and to assess its maternal and neonatal outcome - Syed, Anam B.; Kapote, Deepali S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: There is widespread acceptance of epidural analgesia among many physicians and patients, but disagreement remains regarding the effect of intrapartum epidural analgesia on the subsequent progress of labour and the mode of delivery. This study was designed to look and assess the effects of labour analgesia on maternal and fetal outcomes. Methods: This is an observational prospective cohort study where 60 parturient visiting the hospital in labour during the study period who fulfilled the eligibility criteria & gave written informed consent for the participation were included as cases. Another 60 parturient visiting the hospital during the same period who also fulfilled the eligibility criteria and consent for the same were included as controls. After test dose of 3 ml of 2% lignocaine with 1:2,00,000 adrenaline, an initial bolus of 10 ml of 0.1% Ropivacaine+1microgram/cc Fentanyl is given. Results: Epidural analgesia gave better pain relief when the VAS scores of the two groups were compared. No effect on increase of Caesarean or instrumental delivery rates was observed. Even though the first stage of labour was prolonged and the second stage shortened, the overall time of active stage of labour remained the same in both groups. No adverse neonatal outcome was seen with respect to epidural analgesia. Conclusions: Epidural analgesia provided excellent pain relief for most of the women delivering at our institute & is associated with high patient satisfaction.